Bizarreness of Lucid and Non-lucid Dream: Effects of Metacognition - Yu, Chunyun; Shen, Heyong (Frontiers in Psychology, 2020)
Dreams are usually characterized by primary consciousness, bizarreness and cognitive deficits, lacking metacognition. However, lucid dreaming (LD) is a type of consciousness state during which the dreamer is aware of the fact that he or she is dreaming, without leaving the sleeping state. Brain research have found that LD shares some common neural mechanisms with metacognition such as self-reflection. With a different metacognition level, the bizarreness of LD would also change. However, the difference in bizarreness between LD and non-LD was seldom explored, and individual differences were often neglected. In the present study, considering LD prevalence in Asia was rarely studied and related results in China and Japan were very different from each other, we first investigated the LD frequency of China in a standardized way. On that basis, we collected dreams of subjects who had relatively higher LD frequency and compared Bizarreness Density (BD) of LD and non-LD. Moreover, to explore the relationships of metacognition traits and BD, we also measured self-reflection and insight trait by Self-Reflection and Insight Scale. We found that 81.3% of subjects have experienced LD once or more, which is similar to findings in some western countries. Besides, BD was significantly lower in LD than in non-LD. Self-reflection and insight were inversely associated with dream bizarreness. These findings indicate that self-consciousness traits extend from waking to LD and non-LD state. As a particular consciousness state, LD may shed light on the research of consciousness and dream continuity. Future research on dream bizarreness are suggested to take dream types and metacognition differences into consideration.